2012
DOI: 10.1063/1.3692293
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Renner-Teller effect after core hole excitation in the dissociation dynamics of carbon dioxide dication

Abstract: The fragmentation of the doubly-charged carbon dioxide molecule is studied after photoexcitation to the C 1s12πu and O 1s12πu states using a multicoincidence ion-imaging technique. The bent component of the Renner-Teller split states populated in the 1s→ π* resonant excitation at both the carbon and oxygen 1s ionization edges opens pathways to potential surfaces in highly bent geometries in the dication. Evidence for a complete deformation of the molecule is found in the coincident detection of C+ and \documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
3
25
1
Order By: Relevance
“…This is an additional confirmation that at the lower ion energies the molecular oxygen ion is formed in single ionization with low kinetic energy release, but in double ionization at higher energy. The fact that it is there formed with C + partner ions is not in doubt, as it was observed by Laksman et al 13 who investigated the dynamics in detail, and it is also confirmed here. But if the explanation given above for the formation of high kinetic energy O 2 + is correct, then C + (with O 2 ) ought to be formed by the same mechanism of electron recapture by O 2 + rather than by C + .…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…This is an additional confirmation that at the lower ion energies the molecular oxygen ion is formed in single ionization with low kinetic energy release, but in double ionization at higher energy. The fact that it is there formed with C + partner ions is not in doubt, as it was observed by Laksman et al 13 who investigated the dynamics in detail, and it is also confirmed here. But if the explanation given above for the formation of high kinetic energy O 2 + is correct, then C + (with O 2 ) ought to be formed by the same mechanism of electron recapture by O 2 + rather than by C + .…”
Section: Resultssupporting
confidence: 73%
“…We focus first on the question posed by Laksman et al 13 whose ion-ion coincidence experiment is sensitive only to double (and higher order) ionization processes: is O 2 + produced from one or both of single or double ionization? As a first approach to this question we examine mass spectra coincident with different electrons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations